Prophylactic Administration of Surfactant in Extremely Premature Infants - Lutz Koch; David Frommhold; Bernd Beedgen; Peter Ruef; Johannes Poeschl (Critical Care Research and Practice)
Objective. To investigate whether prophylactic surfactant administration is superior over selective treatment in preterm infants with respiratory distress syndrome (RDS). Methods. In our retrospective analysis, we compared premature infants (23 + 0 to 26 + 6 weeks) receiving 200 mg/kg surfactant (curosurf0𝑥000𝑎𝑒) within five minutes after birth (prophylactic group, 𝑁=31) with those infants who received surfactant therapy for established RDS (selective group, 𝑁=34). Results. Prophylactic therapy significantly decreased the need for mechanical ventilation (74 hours per patient versus 171 hours per patient, resp.). We observed a reduced incidence of interstitial emphysema (0% versus 9%, resp.), pneumothoraces (3% versus 9%, resp.), chronic lung disease (26% versus 38%, resp.), and surfactant doses per patient (1.3 versus 1.8, resp.), although those variables did not reach significance. Conclusion. We conclude that infants under 27 weeks' gestation profit from prophylactic surfactant administration by reducing the time of mechanical ventilation. This in turn could contribute to reduce the risk for mechanical ventilation associated complications, without any detrimental short-term side effects.